Improving the Performance of Input Interfaces Through Scaling and Human Motor Models. (2nd September 2016) - Muñoz, Luis Miguel; Casals, Alicia
Abstract : The performance of interfaces is affected by human factors, which vary from one person to another, and by the inherent characteristics of the various devices involved. A set of techniques has been studied in order to improve the efficiency and efficacy of input interface devices. These techniques are based on the modification of the motor scaling factor, a transformation similar to the known Control-Display ratio (CD ratio). Operation time, the accuracy of the task and user workload are the indicators used in this work. By means of models based on the various human motor behaviors, the improvement of such indicators has been demonstrated. Using some common input interface devices, a number of experiments have been carried out to evaluate the presented methodology. The results show that the overall performance of input interfaces is significantly improved by applying such methodology.